A new chromane derivative from the stem bark of Scyphocephalium ochocoa. (August 2021) - Feuya Tchouya, Guy Raymond; Foundikou, Hibrahim; Nkolo, Paulin; Mabounda Moutsinga, Marc 2; Edou Mba, Derrick Benjamin; Lebibi, Jacques
Abstract: A new chromane, 5, 8-dihydroxy-2-(10′-phenyldecyl)chroman-4-one (1) was isolated from the stem bark of Scyphocephalium ochocoa, along with three known compounds (2 –4 ). The structure of compound 1 was determined with help of spectroscopic data including IR, UV, HREIMS, 1D and 2D NMR (COSY, HMQC and HMBC) experiments. Furthermore, the chemotaxonomic significance of these compounds along with other compounds previously isolated from Scyphocephalium ochocoa was discussed. Graphical abstract: Image 1 Highlights: Scyphocephalium ochocoa is the only Scyphocephalium species already investigated in the literature. Lignans and alkylresorcynols could be obviously considered as chemotaxonomic markers for the genus Scyphocephalium . A new 2, 3-dihydrochromane derivative is isolated from the EtOAc extract of the stem bark of Scyphocephalium ochocoa . 7-hydroxy-3', 4'-methylenedioxyflavan and β-sitosterol are isolated for the first time from the genus Scyphocephalium .